IMPROVING CULTURAL LITERATURE OF PGSD IKIP SILIWANGI STUDENTS THROUGH BHINEKA CARD MEDIA BASED ON CANVA APPLICATION - Muftianti, Agni; Agra, Hana Sakura Putu; Firdaus, Anugrah Ramadhan (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
This research is motivated by the author's concern for elementary school students who are starting to forget Indonesian culture and are more interested in foreign cultures. This is due to the lack of introduction to local culture for students so that students do not know what kinds of cultures exist in Indonesia. The purpose of this research is to improve the literacy skills of students through the diversity card media with the help of the Canva application. The research method used is a quasi-experimental research design with a non-equivalent pretest posttest control group design. Research design is non randomized pretest posttest control group design, according to Levy and J. Ellis (2011) non randomized pretest posttest control group design. The results of the research carried out are 1) learning by applying the diversity card media with the help of the Canva application can improve the cultural literacy skills of PGSD IKIP Siliwangi in elementary social studies internship courses; 2) teaching using Bhinneka card media with the help of the Canva application is better than conventional learning; 3) learning to use the diversity card media with the help of the Canva application requires careful preparation in planning and implementation.